PENGETAHUAN IBU PRIMIGRAVIDA TRIMESTER III TENTANG PERAWATAN PAYUDARA UNTUK PERSIAPAN MENYUSUI DI WILAYAH KERJA PUSKESMAS BANJARMANGU KABUPATEN BANJARNEGARA TAHUN 2010 - Fika Warginingtyas; Feti Kumala Dewi; Indri Heri S (Universitas Harapan Bangsa Purwokerto, 2010)
Background: Breast Care should be performed during pregnancy is the gestation after eightmonths (third trimester) and not after the delivery. In Puskesmas Banjarmangu, as many asfour mothers never breast care. This is because pregnant women lack information aboutbreast care, but it is also due to the low economic level. Objective: To determine theknowledge overview primigravida third trimester of breast care for breastfeedingpreparation in Puskesmas Banjarmangu Banjarnegara district in 2010. Methods: Thisresearch method is quantitative descriptive based on primary data taken using aquestionnaire with a sample size of 32 respondents. Results: Overview of the third trimesterprimigravida knowledge of breast care for breastfeeding preparation in PuskesmasBanjarmangu Banjarnegara regency in 2010 the majority of respondents (40.6%) have asufficient level of knowledge about breast care. Most respondents had high school and 69.2%of them have enough knowledge. Most of the respondents to obtain information from healthworkers and 50% of them have enough knowledge. Most respondents had a job as much as47.2% of whom IRT good knowledge. Conclusion: Most of the mothers in the third trimesterprimigravid Puskesmas Banjarmangu Banjarnegara district has sufficient knowledge. Keywords: Knowledge, primigravida, the third trimester, the breast care